Do Higher Educated People Feel Better in Everyday Life? Insights From a Day Reconstruction Method Study - Dave Möwisch; Annette Brose; Florian Schmiedek (Social Indicators Research, 2020)
Past research has shown a positive association between education and well-being. Much of this research has focused on the cognitive component of well-being (i.e., life satisfaction) as outcome. On the other hand, the affective component, that is, how often and intensively people experience positive affect (PA) and negative affect (NA) in their everyday lives, has received far less attention. Therefore, we examined the association between education and PA and NA in everyday life, with a particular focus on affective experiences at the sub-facet level (based on a structure of NA with multiple factors). We used data from a nationally representative sample (N0.167em=0.167em1647) of the German Socioeconomic Panel Innovation Sample (SOEP-IS), employing the Day Reconstruction Method (DRM) to capture affective experiences of everyday activities. Multilevel structural equation models revealed that (1) education was not related to PA, but (2) was positively associated with two sub-facets of NA (mourning/worries and loneliness/boredom); (3) income might in part explain the association between education and NA; (4) education does not particularly seem to serve as a resource in times of unemployment or retirement (i.e., there were no interactions between education and unemployment/retirement regarding well-being) In essence, higher educated people reported fewer negative emotions in everyday life than their lower educated counterparts, but not more positive emotions. The findings underline that different facets of NA, in addition to life satisfaction, are relevant variables related to education and should receive more attention in order to gain a more comprehensive understanding of non-monetary correlates of education.
Keywords: 300; Education; Affect; Well-being; Day reconstruction method; SOEP-innovation sample